2016
DOI: 10.1016/j.ejogrb.2016.07.490
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control and maternal and fetal outcomes in pregnant women with type 1 diabetes according to the type of basal insulin

Abstract: In this observational study of pregnant women with T1DM, the type of basal insulin was independently associated with metabolic variables and foetal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
13
0
3
Order By: Relevance
“…Previous studies have shown that pre‐pregnancy planning improves gestational outcomes, including A1C . All three cases developed preeclampsia and LGA infants, both being common among women with T1D, with rates of 5%‐34% and 29%‐63%, respectively . This case series cannot assess the adequacy of HCL therapy to improve gestational outcomes, to do so would require a large randomized‐controlled trial.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that pre‐pregnancy planning improves gestational outcomes, including A1C . All three cases developed preeclampsia and LGA infants, both being common among women with T1D, with rates of 5%‐34% and 29%‐63%, respectively . This case series cannot assess the adequacy of HCL therapy to improve gestational outcomes, to do so would require a large randomized‐controlled trial.…”
Section: Discussionmentioning
confidence: 91%
“…[20][21][22] All three cases developed preeclampsia and LGA infants, both being common among women with T1D, with rates of 5%-34% and 29%-63%, respectively. [23][24][25][26][27][28][29][30] This case series cannot assess the adequacy of HCL therapy to improve gestational outcomes, to do so would require a large randomized-controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…Два быстродействующих аналога инсулина, лизпро и аспарт, в настоящее время разрешены к применению у беременных с СД-1 на основании результатов рандомизированных клинических испытаний (РКИ) [12]. В связи с тем, что в многочисленных исследованиях данные препараты показали исходы беременности для матери, плода и новорожденного, аналогичные исходам у пациенток, применяющих обычный человеческий инсулин, аналоги инсулина лизпро и аспарт признаны достаточно безопасными и эффективными, и классифицируются как категория риска для беременности B [13][14][15].…”
Section: прогресс в лечении сд-1 у беременных женщинunclassified
“…Глюлизин -еще один быстродействующий аналог инсулина, доступный для использования в общей диабетической популяции. Тем не менее, нет контролируемых исследований, посвященных его безопасности во время беременности [12], и глюлизин не рекомендуется беременным женщинам с СД-1.…”
Section: прогресс в лечении сд-1 у беременных женщинunclassified
“…. By contrast, women on MDI, who usually use NPH as a basal insulin , may be protected from fetal growth acceleration and hyperglycaemia in the middle of the night, due to the action peak 4 h after the injection of NPH . This possibility of nocturnal hyperglycaemia seems a good argument to perform continuous glucose monitoring during pregnancies complicated by diabetes, and it would be interesting to know whether the type of long‐acting insulin (NPH vs glargine) did influence the outcomes for the participants on MDI in the study by Hauffe et al .…”
mentioning
confidence: 99%